Efficacy of diagnostic testing for allergen sensitization in canine atopic dermatitis: a systematic review - Morales-Romero, Roger; Gonzalez-Dominguez, María S.; Sánchez, Jorge; Correa-Valencia, Nathalia M.; Maldonado-Estrada, Juan G. (Frontiers in Veterinary Science, 2025)
IntroductionCanine atopic dermatitis (CAD) is an important cause of quality of life in dogs and their owners. There are different diagnostic tools to evaluate sensitization to allergens in CAD; however, there is little information to evaluate the clinical usefulness of these tests.MethodsA systematic review aiming to assess the accuracy of allergen sensitization tests in CAD patients was performed. The search was planned, executed, and reported following PRISMA standards. The OVID®/MEDLINE, PubMed®, SciELO, and Redalyc databases were searched to find relevant studies comprising “diagnostic method” (OR test OR diagnosis OR method OR diagnostic OR paraclinic=) AND (atopic = OR hypersensitivity* OR allergen* OR “allergic reaction*” OR atopy) AND (dermatitis OR eczema OR scratching OR prurit = OR erythema OR rash OR edema) AND (canine OR dog* OR bitch* OR pupp*) search. Defined relevant articles were systematized, and content was analyzed via Atlas TI Scientific Software Development Software.ResultsThe groups of diagnostic tests included the intradermal test (IDT), serologic-specific allergen test (SAT), skin prick test (SPT), and patch test. Combining the results from all the search engines and deduplicate elimination, yielded 928 eligible citations published between 1963 and 2024, and the 72 articles that met the eligibility criteria were included in the qualitative synthesis evaluating SAT (n = 36), IDT (n = 37), SPT (n = 2), and patch tests (n = 1) reporting the use of 136 different allergens. Favrot’s clinical criteria were applied in 41.6% of the studies (30/72), with no previous consensus on the case definition for CAD.DiscussionThe results of the review indicate that there is little information available to establish the diagnostic performance of the tests, which makes it difficult to make a recommendation regarding their use. In this systematic review they identified gaps in current knowledge that suggest the need for future research to standardize allergenic extracts, define cutoff points in serological tests, and consider environmental, geographic, and demographic variables. These findings provide a solid basis for improving the diagnosis and management of CAD and guiding future research in this field. Further studies are needed to adequately establish the diagnostic performance of the tests and their actual clinical usefulness.